The water governance systems in Dhaka and metropolitan Manila marginalized women's capabilities and social justice - Ahmed, Sayeed Iftekhar (ProQuest Dissertations & Theses Global, 2009)
"This dissertation explores the effects of the state-led and Public Private Participation (PPP) governance systems for attaining capabilities-pivotal for establishing social justice-over the use of supplied water resources from the perspective of economically marginalized women. In my dissertation, I used Amartya Sen's capability approach, David Crocker's participatory typology, and John Gaventa's power cube model to develop an analytical framework for comparing the water governance systems in Dhaka, Bangladesh, and Metropolitan Manila, Philippines. This framework assesses the effects of governance on water distribution from the perspective of economically marginalized women. This study examines only the political and (basic) material capabilities of economically marginalized women in terms of their participation in the decision making process and attainment of capabilities over the use of supplied water resources. Therefore, this study asks two main questions: How do two different types of governance systems-the state and the PPP-affect the political capability of marginalized women to participate in the spaces where decisions are made regarding the distribution of supplied water resources in Dhaka and Metropolitan Manila? How do these systems affect their basic material capability to access supplied water resources in these two cities? Social justice in water distribution is examined in terms of marginalized women's capabilities to participate in the formal decision-making process and their ability to obtain the minimum quantity, affordable price, and acceptable quality of water. Although qualitative analysis is the basic approach in this research, empirical data are used to operationalize important concepts such as minimal water requirements for poor residents in urban areas. The purpose of combining the two methodologies is to verify the qualitative findings through the empirical scrutiny of quantitative data. The findings suggest that marginalized women have very limited ability to access water under the state-led governance system in Dhaka, but comparatively more ability to access water resources under the PPP governance in Manila. However, women are excluded from the decision-making process under both types of governance systems. The study proposes an alternative for introducing a marginalized women-centered deliberative, reflexive system of governance to increase efficient and equitable distribution of urban water."--Abstract.